Rosai‐Dorfman disease presenting with solitary liver mass without lymphadenopathy: A case report. Issue 8 (25th August 2021) - Roosta, Yousef; Esfahani, Ali; Vahedi, Amir; Tarvirizadeh, Kosar; Asoubar, Sadegh; Boroofeh, Behdad; Dinparast, Roshan; Behzadi, Farhad; Raeisi, Mortaza; Hosseiniazar, Mohammadreza Mohammad
Abstract: Rosai‐Dorfman disease (RDD), as a lymphoproliferative disorder with unknown etiology, is commonly identified with systemic clinical manifestations in various organs. In this case study, RDD occurrence was reported with an exceedingly liver mass. Abstract : Rosai‐Dorfman disease (RDD), as a lymphoproliferative disorder with unknown etiology, is commonly identified with systemic clinical manifestations in various organs. In this case study, RDD occurrence was reported with an exceedingly liver mass.